PEMBUATAN KARBON AKTIF DARI TANDAN KOSONG PISANG KEPOK (Musa paradisiaca L.) DENGAN BANTUAN GELOMBANG ULTRASONIK - Helbyarti Mawar Sari; Noor Hindryawati; R.R. Dirgarini N. (PROSIDING SEMINAR KIMIA, 2017)
Syntheses of activated carbon from empty bunches of kepok banana (MusaParadisiaca L) (TKP) with ultrasonic waves have been done. The of activated carbon were made via three step, namely carbonization at 350 °C, silica extraction with NaOH, activation with H3PO4 and ultrasonic waves exposure (exposure time 30, 60, and 90 minutes). The best quality activated carbons (according to SNI 06-3730-95) were obtained from the process with ultrasonic wave exposure for 90 minute for activated carbon TKP. Respecting the best quality activated carbon TKP has 4.22 % water content, 3.67 % ash content, 17.52 % volatile matter, 74.59 % carbon content and 840.14 mg/g absorption capacity of lodium. The of activated carbon was analyzer characterized by Scanning Electron Microscope (SEM) showed that the pore of activated carbon was more perfectly formed and regular. Analyzer of surface area with Braunanear Elmmelt and Teller (BET) method showed surface area without exposure at TKP that is 35 m2/g with exposure of TKP that is 94 m2/g. Exposure ultrasonic waves increased surface area and facilitated the formation of more pores with ordered form than the non- exposure one. Keywords: Empty bunches banana, carbon, activated H3PO4, and ultrasonic wave